The Impact of Tourism Destinations in Sports Events on the Mental Well-being of Tourists - Weifeng Chang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to better understand the impact of tourism destination imagery on passenger psychological state, the author proposes a study based on the impact of sports event tourism destination imagery on passenger psychological state. The author selected golf open races, sea sailing races, and international marathon races held in a certain province as examples. Using questionnaire survey, literature analysis and mathematical statistics, based on the brand alliance theory, test the relationship between large-scale sports events and the impact of tourism destination brands through reliability and validity analysis, descriptive analysis, and confirmatory factor analysis of questionnaire surveys. A total of 300 valid questionnaires were collected for this survey. The proportion of males and females in the sample is relatively balanced, and the proportion of locals and non locals is also relatively balanced. The respondents are concentrated between the ages of 25-45, accounting for 70% of the sample size. The research results indicate that, the degree of image fit and image extension positively affect brand identity, the degree of image fit and image extension positively affect the image of tourism destinations, and brand identity positively affects the image of tourism destinations. The image of sports events has a significant positive impact on the image of tourism destinations, and the two images can be extended and transferred.